Development of Self-Directed Learning Measurement Model for High School Students in Sekong Province, Lao People’s Democratic Republic: A Confirmatory Composite Analysis - Souliyavong, Noumai; Damrongpanit, Suntonrapot (Journal of Inclusive and Innovative Education, 2024)
This research aims to develop and validate a measurement model of self-directed learning for high school students in the secondary education level (Grades 5 to 7) in the Sekong province, Lao People’s Democratic Republic (Lao PDR). The study, conducted in the first semester of the academic year 2022, sampled 635 students from 7 schools using stratified random sampling. Data collection involved a 5-level Likert scale questionnaire with 48 items. Data analysis utilized Confirmatory Composite Analysis (CCA) with a Formative-Formative, Disjoint Two-stage Approach. The results of the study were as follow revealed that the self-directed learning measurement model comprises 8 components, namely: 1) Openness to learning opportunities, 2) Self-concept as an effective learner, 3) Independence learning, 4) Responsibility for one’s own learning, 5) Love of learning, 6) Creativity, 7) Positive orientation to the future, and 8) Ability to use basic study skills and problem-solving skills. Each component consists of 2 indicators, totaling 16 indicators. The model demonstrated a good fit with the observational data.